Observation of the effectiveness of clinical indicators of cardiac shock wave therapy in patients with ischemic heart disease: A systematic review and meta-analysis - Wu, Xinze; Gu, Minghong; Ma, Yixuan; Song, Peiyu; Fang, Chenghu (Frontiers in Cardiovascular Medicine, 2023)
Objective: Ischemic heart disease (IHD) has a high prevalence and mortality rate, imposing a heavy burden on patients and society, and there is still a need to optimize treatment options for IHD. Cardiac shockwave therapy (CSWT) is gaining popularity as a new treatment for IHD patients. Considering the limited number of clinical studies included in previous reviews, inconsistent methodological quality, and inconclusive results, this meta-analysis aims to assess the effects of CSWT in IHD patients. Methods: 4 English databases and 3 Chinese databases were systematically searched for existing controlled trials of CSWT for IHD from database inception to September 1, 2022. Methodological quality was assessed using the Cochrane Risk of Bias tool. A meta-analysis of comparative effects was performed using Review Manager v.5.4 software. Results: 19 published controlled trials totaling 1254 subjects were included. Results showed that CSWT could enhance left ventricular function and myocardial viability, improve cardiac function and alleviate angina pectoris symptoms. The effects on the SAQ scores and exercise duration were not statistically significant. Conclusions: This systematic review and meta-analysis suggests that CSWT could provide benefits for several clinical indicators of IHD. Further randomized trials with larger sample sizes and of higher methodological quality are needed to confirm these results.